Habitat Study and Breeding Site Potential of Oryctes rhinoceros in Oil Palm Plantations Sei Silau Plantations, Asahan Regency, North Sumatra - Ummi Maysaroh; Anugerah Pustakawan Pradipta; Ira Amelia (Jurnal Riset Perkebunan, 2026)
Oil palm (Elaeis guineensis) is one of the most important plantation crops in tropical regions, yet its productivity is often threatened by the rhinoceros beetle (Oryctes rhinoceros), a major pest that damages growing points and significantly reduces yields. Understanding the habitat and breeding potential of this pest is essential for sustainable management strategies. This study was conducted at Sei Silau Estate, PTPN III, Asahan Regency, to examine potential breeding sites of O. rhinoceros in immature plants (TBM), mature plants (TM), and empty fruit bunches (EFB). A total of 381 individuals were collected, with the highest population found in TM (206 individuals), followed by EFB (107 individuals) and TBM (68 individuals). The larval stage dominated up to 88.19%, particularly the third instar. These findings indicate that organic materials such as fronds, decaying trunks, and EFB are highly suitable habitats supporting the life cycle of O. rhinoceros. Therefore, organic waste management is essential for sustainable pest control, while manual hunting can serve as a complementary strategy within an integrated pest management framework in oil palm plantations.